Natural products from plants and microorganisms: Novel therapeutics for chronic kidney disease via gut microbiota regulation - Zheng, Lin; Luo, Mingjing; Zhou, Haokui; Chen, Jianping (Frontiers in Pharmacology, 2023)
Dysbiosis of gut microbiota play a fundamental role in the pathogenesis and development of chronic kidney disease (CKD) and its complications. Natural products from plant and microorganism can achieve recognizable improvement in renal function and serve as an alternative treatment for CKD patients for a long history, yet less is known on its beneficial effects on the kidney injury by targeting the intestinal microbiota. In this review, we summarize studies on the effects of natural products from plant and microorganism, including herbal medicines and their bioactive extracts, polysaccharide from plant and microorganism, phytochemicals etc., in the prevention and treatment of CKD through targeting gut microflora. We describe the strategies of these anti-CKD effects in animal experiments including re-modulation of gut microbiota structure, reduction of uremic toxins, enhancement of short chain fatty acids (SCFAs) production, regulation of intestinal inflammatory signaling and improvement of intestinal integrity. Meanwhile, the clinical trials of different natural products in CKD clinical practice were also analyzed and discussed. These provide information to enable a better understanding of the reno-protective effects of these effective natural products from plant and microorganism in the treatment of CKD. Finally, we propose the steps to prove the causal role of the intestinal microflora in the treatment of CKD by natural products from plant and microorganism. We also assess the future perspective that natural active products from plant and microorganism can beneficially delay the onset and progression of kidney disease by targeting the gut flora, and highlight the remaining challenges in this area. Continuous deepen studies in recent years proved that gut microbiota is a potential target of natural active products from plant and microorganism for CKD treatment. Fully understanding the functions and mechanisms of gut microbiota in these natural active products from plant and microorganism is conducive to their application as an alternative therapeutic in CKD treatment.